Non-Communicable Diseases in Jamaica : Moving from Prescription to Prevention - Chao, Shiyan; Carpio, Carmen; Geyndt, Willy de (World Bank, Washington, DC, 2012)
Reducing the burden of Non-communicable diseases (NCDs) in Jamaica is a national policy. The Government of Jamaica has recognized the importance of preventing and controlling NCDs and created the National Health Fund (NHF) to reduce the cost of treating them by providing free or subsidized medicines to patients with NCD conditions and finance some prevention programs. The World Bank undertook a study to learn from Jamaica's experience in tackling major NCDs and related risk factors, provide policy options for Jamaica to improve the NCD Program, and share with other Caribbean countries lessons learned from this experience. The study answered three questions: (i) whether Jamaica's NHF and its drug subsidy Program have reduced out of pocket spending on NCD treatment; (ii) whether access to treatment of NCDs has improved in the country; and (iii) what is the economic burden on patients with NCDs and their families.